Approaching hell’s kitchen: Molecular daredevil clouds in the vicinity of Sagittarius A - Moser, Lydia; Sánchez-Monge, Álvaro; Eckart, Andreas; Requena-Torres, Miguel A.; García-Marin, Macarena; Kunneriath, Devaky; Zensus, Anton; Britzen, Silke; Sabha, Nadeen; Shahzamanian, Banafsheh; Borkar, Abhijeet; Fischer, Sebastian (Astronomy and astrophysics (Berlin), 2017)
We report serendipitous detections of line emission with the Atacama Large Millimeter/submillimeter Array (ALMA) in bands 3, 6, and 7 in the central parsec down to within 1′′ around Sgr A* at an up to now highest resolution (<0.5′′) view of the Galactic center (GC) in the submillimeter (sub-mm) domain. From the 100 GHz continuum and the H39α emission we obtain a uniform electron temperature around Te ~ 6000 K for the minispiral. The spectral index (S ∝ να) of Sagittarius A* (Sgr A*) is ~0.5 at 100–250 GHz and ~0.0 at 230–340 GHz. The bright sources in the center show spectral indices around –0.1 implying Bremsstrahlung emission, while dust emission is emerging in the minispiral exterior. Apart from CS, which is most widespread in the center, H13CO+, HC3N, SiO, SO, C2H, CH3OH, 13CS and N2H+ are also detected. The bulk of the clumpy emission regions is at positive velocities and in a region confined by the minispiral northern arm (NA), bar, and the sources IRS 3 and 7. Although partly spatially overlapping with the radio recombination line (RRL) emission at same negative velocities, the relation to the minispiral remains unclear. A likely explanation is an infalling clump consisting of denser cloud cores embedded in diffuse gas. This central association (CA) of clouds shows three times higher CS/X (X: any other observed molecule) ratios than the circumnuclear disk (CND) suggesting a combination of higher excitation, by a temperature gradient and/or infrared (IR) pumping, and abundance enhancement due to UV and/or X-ray emission. Hence, we conclude that this CA is closer to the center than the CND is to the center. Moreover, we find molecular line emission at velocities up to 200 km s-1. Apart from the CA, we identified two intriguing regions in the CND. One region shows emission in all molecular species and higher energy levels tested in this and previous observations and contains a methanol class I maser. The other region shows similar behavior of the line ratios such as the CA. Outside the CND, we find the traditionally quiescent gas tracer N2H+ coinciding with the largest IR dark clouds in the field. Methanol emission is found at and around previously detected methanol class I masers in the same region. We propose to make these particular regions subject to further studies in the scope of hot core, cold core, and extreme photon and/or X-ray dominated region (PDR/XDR) chemistry and consequent star formation in the central few parsecs.